Concordance Among In-Vivo Reflectance Confocal Microscopy, Trichoscopy, and Histopathology in the Evaluation of Alopecia Areata Incognita - Starace, Michela; De Carvalho, Nathalie; Fernandes Melo, Daniel; Cedirian, Stephano; Desmond Mandel, Victor; Machado, Carla Jorge; Misciali, Cosimo; Pellacani, Giovani; Piraccini, Bianca Maria; Ardigò, Marco (Dermatology Practical & Conceptual, 2024)
Introduction: Alopecia areata incognita is a non-scarring autoimmune hair loss condition primarily affecting women aged 20 to 40. It is often misdiagnosed due to its resemblance to other conditions. Diagnosis relies on clinical suspicion, trichoscopic findings, and histological features. Reflectance confocal microscopy (RCM) shows promise as a noninvasive diagnostic tool for alopecia areata incognita. Objective: In this study, we aimed to explore RCM’s diagnostic potential by investigating its association with trichoscopic and histopathological findings. Methods: We conducted a prospective study with 12 female patients affected by alopecia areata incognita. Patient data, trichoscopy, and RCM were used for diagnosis. Biopsies were taken based on trichoscopic and RCM criteria. Agreement between RCM, trichoscopy, and histopathology was assessed. Results: RCM showed substantial agreement with histopathology for fibrous tracts (92.9%). Other criteria, like infundibular ostia and inflammation, exhibited reasonable agreement (71.4% to 78.6%), with varying Kappa values. Miniaturized follicles had the lowest agreement (64.3%). Conclusion: This paper suggests that RCM holds promise as a diagnostic tool for alopecia areata incognita, offering advantages in non-invasiveness and real-time monitoring. It demonstrated substantial agreement with histopathology in identifying key features. While some discrepancies were noted, especially in detecting inflammatory infiltrates, further research may enhance RCM's sensitivity. The non-invasive nature of RCM could improve patient experiences and offer dynamic disease tracking for better treatment decisions. This technology's potential extends beyond alopecia areata incognita, presenting opportunities for more patient-friendly diagnostic procedures in trichology.